THE EMBODIMENT OF EFFICIENCY-JUSTICE PRINCIPLE IN INDONESIAN RETAIL REGULATIONS - Tulandi, Edwin Steven; Suhariningsih, Suhariningsih; Sihabudin, Sihabudin; Winarno, Bambang (Faculty of Law, Universitas Brawijaya, 2017)
Retail regulations is one of national sector which is impacted by globalization on the legal aspects in Indonesia. The dynamics of the traditional retail (traditional market and mom and pop store) management in some areas tend to have an orientation on increasing local revenue which can be seen in the management of irregular traditional market management and transition of traditional market to the private sector. On the other hand, the proliferation of modern retail which is side by side with traditional retail is a form of arrangement that is not in accordance with the retail 's designation/purpose. This indicates that the efficiency-justice principle that aims to create a balance turns more to the efficiency of the exclusion of justice for traditional retail. This paper aims to analyze the embodiment of Efficiency-Justice Principle in Indonesian Retail Regulations. The method used in this research is normative-juridical method, which analyze existing national retail regulations. It proposes appropriate method in embodying Efficiency-Justice Principle in Indonesian Retail Regulations.